Pengaruh kepemimpinan kepala sekolah Dan sarana belajar terhadap prestasi Belajar matematika - Nurdin Nurdin; Munzir Munzir (Faktor Jurnal Ilmiah Kependidikan, 2017)
Abstract : This study aims to determine the magnitude of the influence of principal leadership and learning tools on mathematics learning achievement. Research Method is survey research. The subject of this research are 80 students taken randomly at SMP Negeri 1 Tambun Bekasi. Data collected by questionnaire instrument using Likert skla. Validity of data obtained by validity and reliability test, all data have normal distribution. The result of research indicate that principal leadership give significant influence to mathematics learning achievement. Likewise the means of learning give a significant influence on the achievement of learning mathematics. The coefficient of determination (R)2 is the principal's leadership and the means of learning have a moderate relationship to the mathematics learning achievement. Keywords: Leadership, Means, Achievement